ANALISIS PENJADWALAN KANAL UPLINK LONG TERM EVOLUTION (LTE) MENGGUNAKAN ALGORITMA ROUND ROBIN - Islami, Fernesia Dini; Purnomowati, Endah Budi; Yuwono, Rudy (Jurnal Mahasiswa TEUB, 2020)
Abstract— Single Carrier - Frequency Division Multiple Access (SC-FDMA) technology is a multiple access technique used in the Long Term Evolution (LTE) channel uplink. SC-FDMA has a transmission block called resource block, the transmission block will be assigned to the user. A scheme to allocate resource block power is needed so that each resource block can work optimally, for example the round robin algorithm. Round Robin algorithm allocates resource block fairly with each user. This research was conducted in simulation with Matlab which aims to determine the effect of using the round robin algorithm compared to Proportional Fair and Maximum Throughput algorithm as the allocation of the resource blocks. Performance parameters based on fairness values. The results showed that the fairness was better in the round robin algorithm than Proportional Fair and Maximum Throughput algorithm. Index Terms—SC-FDMA, LTE, Round Robin